2020
DOI: 10.1152/ajpendo.00145.2020
|View full text |Cite
|
Sign up to set email alerts
|

Worsening baroreflex sensitivity on progression to type 2 diabetes: localized vs. systemic inflammation and role of antidiabetic therapy

Abstract: Cardiac autonomic neuropathy (CAN) is an early cardiovascular manifestation of type 2 diabetes (T2D) that constitutes an independent risk factor for cardiovascular mortality and morbidity. Nevertheless, its underlying pathophysiology remains poorly understood. We recently showed that localized perivascular adipose tissue (PVAT) inflammation underlies the incidence of parasympathetic CAN in prediabetes. Here, we extend our investigation to provide a mechanistic framework for the evolution of autonomic impairmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 69 publications
(109 reference statements)
5
27
0
Order By: Relevance
“…Indeed, IF (15 or 39 h fast) was found to augment AMPK phosphorylation in rats (Kajita et al, 2008). Significantly, not only has our work shown a reduced AMPK activity in cardiovascular impairment associated with early metabolic dysfunction involving PVAT inflammation in HFD-fed rats (Al-Assi et al, 2018), our results also demonstrated autophagy suppression as a possible contributor to the observed phenotype (Bakkar et al, 2020b;Fakih et al, 2020). Moreover, a lack of AMPK activity was implicated in AC hypertrophy (Villena et al, 2004).…”
Section: Adipose Tissue Remodeling In Response To Therapeutic or Intermittent Fastingsupporting
confidence: 54%
See 2 more Smart Citations
“…Indeed, IF (15 or 39 h fast) was found to augment AMPK phosphorylation in rats (Kajita et al, 2008). Significantly, not only has our work shown a reduced AMPK activity in cardiovascular impairment associated with early metabolic dysfunction involving PVAT inflammation in HFD-fed rats (Al-Assi et al, 2018), our results also demonstrated autophagy suppression as a possible contributor to the observed phenotype (Bakkar et al, 2020b;Fakih et al, 2020). Moreover, a lack of AMPK activity was implicated in AC hypertrophy (Villena et al, 2004).…”
Section: Adipose Tissue Remodeling In Response To Therapeutic or Intermittent Fastingsupporting
confidence: 54%
“…Limited changes in the status of immune cell and adipokine secretome of these depots could be sufficient to exert profound effects on cardiovascular structure and function. Interestingly, this highlights the importance and potential utility of IF protocols in the cardiovascular outcome of early metabolic impairment where adipose inflammation plays a more important role vs. hyperglycemia being a more predominant factor in more advanced conditions of metabolic decompensation in diabetes (Elkhatib et al, 2019;Bakkar et al, 2020b).…”
Section: Cardiometabolic Syndrome and Therapeutic Or Intermittent Fastingmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypercaloric diet composition was based on our previous studies showing that a 12‐week feeding of an hypercaloric diet, offering ≈39% calories from fat with a 5% saturated fat content by weight, led to a nonobese prediabetic phenotype. 13 , 14 , 18 , 34 , 35 A loss of 50% of the Pi content was assumed in the previous studies because of nutrient displacement during preparation. The 2 additional groups were fed a hypercaloric diet with phosphorus content of 0.75 (Group 3; hypercaloric: 0.75) and 1.5 mg/kcal (Group 4; hypercaloric: 1.5), which are equal to and twice as much as the AIN‐recommended content.…”
Section: Methodsmentioning
confidence: 99%
“… 14 In our hands, hyperinsulinemia, dyslipidemia, and localized adipose tissue inflammation (perivascular and perirenal) were consistent observations in the rat model receiving this diet. 14 , 18 , 35 , 46 The modification of the added amounts of starch, sucrose, and oil were necessary to maintain consistency as the amount of other semisolids and powders changed, as well as achieve the desired calorie density.…”
Section: Methodsmentioning
confidence: 99%